Cuidado de enfermería y satisfacción del paciente prequirúrgico del Hospital Víctor Lazarte Echegaray - Quispe Perez, Pierina Vanessa (2019)
The correlational descriptive research was carried out in the surgery department of the Victor Lazarte Echegaray Hospital between January and July with the purpose of determining the relationship between nursing care and the satisfaction of the mature adult presurgical patient hospitalized who applied two instruments, one referring to the quality of nursing care and the second referring to the of satisfaction of the hospitalized presurgical patient, for the relationship of the variables the statistical test of the chi-square was used, reaching the following results: 80 percent of the patients report receiving regular nursing care quality in the scientific / technical component, 72.5 percent in the interpersonal component and 75 percent in the environment. The 72.5 percent of patients report dissatisfaction in safety activities, 67.5 percent in courtesy, 60.0 percent in communication, 57.5 percent in competent, and 52.5 percent in credibility and report feeling satisfied with the quality of care received with 47.5 percent in the credibility activity, 42.5 percent in the competent activity, 40.0 percent in communication and 32.5 and 27.5 percent in the areas of courtesy and security. There is a significant relationship between nursing care and the satisfaction of the mature adult pre-surgical patient and when applying the statistical test of independence of chi-square criteria both variables Χ² 7.569 p = 0.0127